2021
DOI: 10.18535/ijmsci/v8i07.02
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Helicobacter Pylori Antibody among Outpatients of Federal Medical Center, Yenagoa, Niger Delta Region of Nigeria

Abstract: Helicobacter Pylori is the most common chronic bacterial infection (acquired early childhood) in humans affecting 50% of the world population and much attention has not been paid to this. This study was carried out between February and October 2019 to test for the presence of Helicobacter Pylori antibody among asymptomatic individuals attending Federal Medical Center, Yenagoa, Bayelsa State. A total of 200 {114(57%) males, 86(43%) females} blood samples were collected at ramdom into Ethylene diamine tetraaceti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…The disparity in temperature observed across the locations studied may be due to variations in ambient temperature at the time of sampling and analysis [54]. In a related study, Reuben et al [31] obtained a temperature ranging from 24.80 to 27.00 0 C. Raji et al [55] and Olorode et al [56] reported the temperature range of 25.30 to 29.20 0 C from River Sokoto, and 25.00 to 28.00 0 C from five different Rivers in Port Harcourt respectively.…”
Section: Resultsmentioning
confidence: 93%
“…The disparity in temperature observed across the locations studied may be due to variations in ambient temperature at the time of sampling and analysis [54]. In a related study, Reuben et al [31] obtained a temperature ranging from 24.80 to 27.00 0 C. Raji et al [55] and Olorode et al [56] reported the temperature range of 25.30 to 29.20 0 C from River Sokoto, and 25.00 to 28.00 0 C from five different Rivers in Port Harcourt respectively.…”
Section: Resultsmentioning
confidence: 93%